Karakteristik epidemologi ibu hamil dengan infeksi human immunodeficiency virus di RSUP Sanglah Denpasar periode Januari 2014 - Desember 2017 - Komang Juni Artawan; I Wayan Artana Putra (Intisari Sains Medis, 2020)
Introduction: The cumulative rate of AIDS in pregnant women in the world is reported to increase dramatically, giving the consequent increase in morbidity and mortality from mothers and children. The purpose of this study is to provide a descriptive picture of pregnant women with HIV in Sanglah Hospital Denpasar during the period January 2014 to December 2017.Methods: This study used a descriptive retrospective design in the population of pregnant women with HIV in Sanglah Hospital Denpasar during the period January 2014 to December 2017.Results: During the study period a total of 218 cases of mothers with HIV were obtained in Sanglah Hospital Denpasar, with the majority characteristics being 20-29 years (56.80%), with the most dominant parity being 1 (48.16%), multipartner husband risk factors (56.43), housewife occupation (63.76%), origin of the area found in Jebmbrana Regency (20.64%), referral origin of Jembrana Regional Hospital (24.31%), age >28 weeks of pregnancy (47.70%), duration of antiretroviral therapy ≥6 months (55.51%), clinical stage I (79.35%), birth method of caesarean section (70.22%), birth weight of children >2500 grams (82.58% ), experienced mild anemia (Hb 9.5 to 10.9 g/dL) (84.12%), an undetectable viral load (66.7%), and a CD4 count of 200-500 / mm3 (49.08%) .Conclusion: HIV prevalence in pregnant women which has an increasing trend in Bali requires more attention from all lines, not only from health workers, but government involvement and public education are needed to prevent new cases of pregnant women with HIV infection.  Pendahuluan: Angka kumulatif AIDS pada wanita di dunia dilaporkan meningkat secara dramatis, memberikan konsekuensi peningkatan akan morbiditas dan mortalitas dari ibu dan anak. Tujuan dari penelitian ini adalah memberikan gambaran deskriptif pada ibu hamil dengan HIV di RSUP Sanglah Denpasar selama periode Januari 2014 hingga Desember 2017.Metode: Penelitian ini menggunakan rancangan retrosepktif deskriptif pada populasi ibu hamil dengan HIV di RSUP Sanglah Denpasar selama periode Januari 2014 hingga Desember 2017.Hasil: Selama periode studi didapatkan total 218 kasus ibu dengan HIV di RSUP Sanglah Denpasar, dengan karakteristik mayoritas berupa 20-29 tahun (56,80%), dengan paritas paling dominan adalah para 1 (48,16%), faktor risiko suami multipartner (56,43), pekerjaan ibu rumah tangga (63,76%), asal daerah ditemukan Kabupaten Jebmbrana (20,64%), asal rujukan RSUD Jembrana (24,31%), usia >28 minggu kehamilan (47,70%), lama terapi ARV ≥6 bulan (55,51%), stadium klinis I (79,35%), metode kelahiran seksio caesaria (SC) (70,22%), berat lahir anak >2500 gram (82,58%), mengalami anemia ringan (Hb 9,5- 10,9 g/dL) (84,12%), viral load tidak terdeteksi (66,7%), dan hitung CD4 200-500 /mm3 (49,08%).Simpulan: Prevalensi HIV pada ibu hamil yang memiliki tren semakin meningkat di Bali membutuhkan perhatian lebih dari segala lini, tidak hanya dari tenaga kesehatan, namun keterlibatan pemerintah serta edukasi masyarakat sangat dibutuhkan untuk mencegah timbulnya kasus baru ibu hamil dengan infeksi HIV.